Papez Circuit Observed by in vivo Human Brain With 7.0T MRI Super-Resolution Track Density Imaging and Track Tracing - Choi, Sang-Han; Kim, Young-Bo; Paek, Sun-Ha; Cho, Zang-Hee (Frontiers in Neuroanatomy, 2019)
The Papez circuit has been considered as an important anatomical substrate involved in emotional experience. However, the circuit remains difficult to elucidate in the human brain due to the resolution limit of current neuroimaging modalities. In this article, for the first time, we report the direct visualization of the Papez circuit with 7-Tesla super-resolution magnetic resonance tractography. Two healthy, young male subjects (aged 30 and 35 years) were recruited as volunteers following the guidelines of the institutional review board (IRB). Track density imaging (TDI) generation with track tracing was performed using MRtrix software package. With these tools, we were able to visualize the entire Papez circuit. We believe this is the first study to visualize the complete loop of the Papez circuit, including the perforant path (PP), thalamocortical fibers of the anterior nucleus (AN), and mammillothalamic tract (MTT), which were hitherto difficult to visualize by conventional imaging techniques.